Q. 44.4( 18 Votes )

# In each of the question, show that the given differential equation is homogeneous and solve each of them.

(x^{2} – y^{2})dx + 2xy dy = 0

Answer :

Here, putting x = kx and y = ky

= k^{0}.f(x,y)

Therefore, the given differential equation is homogeneous.

To solve it we make the substitution.

y = vx

Differentiating eq. with respect to x, we get

Integrating both sides, we get

Put 1 + v^{2} = t

2vdv = dt

log(t)

∴ log(1 + v^{2}) = -logx + logC (∴ From (i) eq.)

The required solution of the differential equation.

Rate this question :

Solve the following differential equation:

RD Sharma - Volume 2

tan^{-1}x + tan^{-1} y = c is the general solution of the differential equation:

The number of solutions of when y(1) = 2 is:

Mathematics - ExemplarFind the particular solution of the differential equation

given that when

Mathematics - Board PapersSolve the following differential equation:

dy + (x + 1)(y + 1) dx = 0

RD Sharma - Volume 2Find the particular solution of the following differential equation:

when x = 1

Mathematics - Board Papers